A comprehensive review of the biodiversity of freshwater fish species in Valleys worldwide and in the Kingdom of Saudi Arabia - Altowairqi, Tahani K; Shafi, Manal E (Journal of Advanced Veterinary and Animal Research, 2024)
An overview of freshwater fish variety worldwide and the variables influencing trends in variation between and within river basins are given in this review. Continental freshwater ecosystems are highly diverse and species-rich, housing nearly 18,000 species of fish (>50% of all fish species) in <0.5% of the total land area and providing a negligible (<0.01%) share of the planet’s water supply. Large lowland tropical river basins such as the Amazon, Congo, and Mekong basins are home to the greatest freshwater fish diversity. Freshwater species of fish depth variation at the global magnitude is correlated with the total amount and variation of aquatic habitats and the environment’s equilibrium overtime during the evolution of scales. The river continuum concept states that there is a predictable shift in fish species depth, diversity of species, and functional characteristics along gradients of environment from headwater to estuary. The ongoing trade of minerals and organic matter related to nearby floodplains is a strong factor in the number and variety of riverine fishes in most parts of the world (the flood pulse concept). Without coordinated conservation efforts, freshwater fishes will suffer significant losses in abundance and diversity due to the numerous threats they currently face worldwide. However, further development, adaptation, training, and guidance are needed. New technologies based on water conservation, suitable species, and local traditions are needed. Waste materials and local feed additives can also be used. Farmers should be provided with the necessary training and information. Adv. Vet. Anim. Res., 11(2): 356-366, June 2024 http://doi.org/10.5455/javar.2024.k784